2012
DOI: 10.3136/fstr.18.617
|View full text |Cite
|
Sign up to set email alerts
|

Moisture Sorption Isotherm of Durum Wheat Flour

Abstract: The moisture sorption isotherms of durum semolina were observed in the temperature range of 30 to 80℃ for both the sorption and desorption processes. The isotherms of its constituent starch and gluten were observed at 30℃ and that of spaghetti was observed at 60℃. All the isotherms were well expressed by the Guggenheim-Anderson-de Boer equation. The isotherm for the desorption process lay over that for the sorption one at any temperature, and a slight hysteresis was recognized. Isosteric heats, q, for sorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 12 publications
3
4
0
Order By: Relevance
“…This is attributed to the fact that, as the moisture content increases, the availability of sites for sorption of water diminish and sorption occurs on the less active sites, giving rise to lower heats of sorption . These findings are in accordance with those of recent investigations, on chestnut and wheat flours , on Chinese wheat varieties , on Spanish whole wheat flour , and on Japanese durum wheat flour .…”
Section: Resultssupporting
confidence: 90%
“…This is attributed to the fact that, as the moisture content increases, the availability of sites for sorption of water diminish and sorption occurs on the less active sites, giving rise to lower heats of sorption . These findings are in accordance with those of recent investigations, on chestnut and wheat flours , on Chinese wheat varieties , on Spanish whole wheat flour , and on Japanese durum wheat flour .…”
Section: Resultssupporting
confidence: 90%
“…In addition, a number of works also show similar results. 13,14,30 This comparative analysis with other studies indicates the reliability of the results obtained in this paper and the assumptions made.…”
Section: Discussionsupporting
confidence: 74%
“…These data are useful for understanding the phenomena that occur during the drying or rehydration of food. 14 The equilibrium moisture content allows to optimize the drying time and energy use. In addition, the data gained may be useful for assessing storage stability of food products.…”
Section: Introductionmentioning
confidence: 99%
“…149) A further study showed that the moisture sorption and desorption isotherms of durum semolina for a temperature range of 30-80°C were well expressed by the Guggenheim-Anderson-de Boer equation; while the desorption isotherm could be overlaid with the sorption one at any temperature, a slight hysteresis was observed. 150) Meanwhile, the partial molar volume of water sorbed to durum wheat flour was measured by dilatometry, which showed that the volume increased with moisture content and reached a constant value of about 17.5 cm 3 /mol at 0.2 kg-H 2 O/kg-d.m. 151) Water sorption of pasta The temperature dependency of equilibrium moisture content and initial sorption rate in spaghetti indicated that the former is limited by starch gelatinization and the latter is governed by diffusion through pores, a process independent of starch gelatinization.…”
Section: Drying Of Pastamentioning
confidence: 99%